Beyond 1995: Negotiating a New United Nations Through Article - Ponzio, Richard J. (Tufts Archival Research Center, 2005)
Volume 20, Issue 1. Winter/Spring The United Nations was created to manage a world that no longer exists. The U.N. Charter should be reviewed and changed to reflect contemporary realities.